Microfluidic antibody profiling after repeated SARS-CoV-2 vaccination links antibody affinity and concentration to impaired immunity and variant escape in patients on anti-CD20 therapy - Priddey, Ashley; Chen-Xu, Michael Xin Hua; Cooper, Daniel James; MacMillan, Serena; Meisl, Georg; Xu, Catherine K.; Hosmillo, Myra; Goodfellow, Ian G.; Kollyfas, Rafael; Doffinger, Rainer; Bradley, John R.; Mohorianu, Irina I.; et al. (Frontiers in Immunology, 2024)
Background: Patients with autoimmune/inflammatory conditions on anti-CD20 therapies, such as Rituximab, have suboptimal humoral responses to vaccination and are vulnerable to poorer clinical outcomes following SARS-CoV-2 infection. We aimed to examine how the fundamental parameters of antibody responses, namely affinity and concentration, shape the quality of humoral immunity after vaccination in these patients.We performed in depth antibody characterisation in sera collected four to six weeks after each of three vaccine doses to wild-type (WT) SARS-CoV-2 in Rituximabtreated primary vasculitis patients (n=14) using Luminex and pseudovirus neutralisation assays, whereas a novel microfluidic-based immunoassay was used to quantify polyclonal antibody affinity and concentration against both WT and Omicron (B.1.1.529) variants.Comparative antibody profiling was performed at equivalent time points in healthy individuals after three antigenic exposures to WT SARS-CoV-2 (one infection and two vaccinations; n=15) and in convalescent patients after WT SARS-CoV-2 infection (n=30).Results: Rituximab-treated patients had lower antibody levels and neutralisation titres against both WT and Omicron SARS-CoV-2 variants compared to healthy individuals. Neutralisation capacity was weaker against Omicron versus WT both in Rituximab-treated patients and in healthy individuals. In the Rituximab cohort, this was driven by lower antibody affinity against Omicron versus WT (median [range] KD: 21.